Characterizing the role of the pre‐SMA in the control of speed/accuracy trade‐off with directed functional connectivity mapping and multiple solution reduction. Issue 6 (19th December 2018) - Weigard, Alexander; Beltz, Adriene; Reddy, Sukruth Nagarimadugu; Wilson, Stephen J.
Abstract: Several plausible theories of the neural implementation of speed/accuracy trade‐off (SAT), the phenomenon in which individuals may alternately emphasize speed or accuracy during the performance of cognitive tasks, have been proposed, and multiple lines of evidence point to the involvement of the pre‐supplemental motor area (pre‐SMA). However, as the nature and directionality of the pre‐SMA's functional connections to other regions involved in cognitive control and task processing are not known, its precise role in the top‐down control of SAT remains unclear. Although recent advances in cross‐sectional path modeling provide a promising way of characterizing these connections, such models are limited by their tendency to produce multiple equivalent solutions. In a sample of healthy adults ( N  = 18), the current study uses the novel approach of Group Iterative Multiple Model Estimation for Multiple Solutions (GIMME‐MS) to assess directed functional connections between the pre‐SMA, other regions previously linked to control of SAT, and regions putatively involved in evidence accumulation for the decision task. Results reveal a primary role of the pre‐SMA for modulating activity in regions involved in the decision process but suggest that this region receives top‐down input from the DLPFC. Findings also demonstrate the utility of GIMME‐MS and solution‐reduction methods for obtaining valid directional inferences from connectivity path models.